Endometriosis and Infertility: How and When to Treat? - Fadhlaoui, Anis; Bouquet de la Jolinière, Jean; Feki, Anis (Frontiers in Surgery, 2014)
Endometriosis is defined as the presence of endometrial-like tissue (glands or stroma) outside the uterus, which induces a chronic inflammatory reaction. Although endometriosis impairs fertility, it does not usually completely prevent conception. The question of evidence based-medicine guidelines in endometriosis-associated infertility is week in many situations. Therefore, we will highlight in this issue where the challenges are.